Iliofemoropopliteal deep vein thrombosis in a patient with a pelvic horseshoe kidney treated successfully with local intravenous lysis therapy and venous stenting - Mikolaj Walensi, MD, MA; Basem Abdelrahman, MD; Pavlos Drongitis, MD; Kai Nassenstein, MD; Abdalla Marei, MD; Johannes N. Hoffmann, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Horseshoe kidney (HSK) is a rare disorder and may be associated with several vascular complications. A 46-year-old female patient with a pelvic HSK suffered a deep vein thrombosis of the left popliteal, femoral, and iliac veins. Lysis therapy, followed by balloon angioplasty and stent implantation in the iliac vein, was performed, significantly improving the patient's symptoms. Endovascular therapies such as lysis therapy and stent implantation may result in excellent therapeutic outcomes for deep vein thrombosis caused by an HSK, sparing the patient extensive surgical procedures on the venous system and, at the same time, reducing the risk of a post-thrombotic syndrome.